Pengaruh sistem prosedur, sarana prasarana dan disiplin kerja terhadap kepuasan masyarakat pada UPTD Puskesmas Baru Kecamatan Dusun Selatan Kabupaten Barito Selatan di Buntok - Wahyuni, Wahyuni; Ritawaty, Noor (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the effect of procedure systems, infrastructure and work discipline on community satisfaction in UPTD Puskesmas Baru, Kecamatan Dusun Selatan in Kabupaten Barito Selatan. This research method is quantitative, data obtained by distributing questionnaires. The population in this study were UPTD Puskesmas Baru patients Kecamatan Dusun Selatan South Barito Regency. The sample is 65, the analysis technique uses the Community Satisfaction Index and Multiple Linear statistical methods as measured using PSPP software. The results of this study from the results of the calculation of the Community Satisfaction Index found that the service quality of UPTD Puskesmas Baru, Dusun Selatan Subdistrict, South Barito Regency is B or rated as Good. The results of this study indicate that the variable System Procedure on Community satisfaction does not have a significant effect and the variable Infrastructure, Work Discipline has anmany effect on community satisfaction at UPTD Puskesmas Baru, Dusun Selatan Subdistrict, South Barito Regency.